The expression of matrix metalloproteinases in intrahepatic cholangiocarcinoma, hilar (Klatskin tumor), middle and distal extrahepatic cholangiocarcinoma, gallbladder cancer, and ampullary carcinoma: Role of matrix metalloproteinases in tumor progression - Hale KIRIMLIOĞLU; İlknur TÜRKMEN; Nuray BAŞSÜLLÜ; Abuzer DİRİCAN; Neşe KARADAĞ; Vedat KIRIMLIOĞLU (Turkish Journal of Gastroenterology, 2019)
-